الخلع في القانون الجزائري - • أحلام سلمان • فايد ميادة (جامعة المسيلة, 2022)
دفعا بالمشرع الجزائري إلى إرساء روح المساواة و تجسيد العدالة، منح للمرأة الحق في إنهاء الرابطة الزوجية التي أصبحت لا تطيقها بسبب كرهها و نفورها منه و ذلك مقابل حق الرجل بإيقاع الطلاق فقد فتح لها باب لاقتداء نفسها بمقابل مالي تدفعه عليه شرعا و قانونا، طريق منصوص للزوج و هو ما يعرف بالخلع الذي يعتبر ويستوجب الوقوع الخلع شروط معينة، كما أن المرأة المخالعة أن تتبع الإجراءات الخاصة برفع الدعوى من أجل الحكم لها بالخلع و الذي يرتب آثار عامة يشترك فيها مع بقية طرق فك الرابطة الزوجية وأثار خاصة ينفرد بها. Summary: In order to establish the spirit of equality and the embodiment of justice, the Algerian legislator was granted the right to terminate the marital bond that she became unable to tolerate because of her hatred and aversion to it, in exchange for the right of the man to divorce, he opened a door for her to borrow herself in return for money paid by law and law, a way stipulated for the husband, which is known as the khula, which is considered and the obligation to fall dislocated certain conditions, and the woman who is deceived to follow the procedures for filing the case in order to judge her Dislocation, which arranges general effects that it shares with the rest of the methods of dismantling the marital bond and has special effects unique to it.
Keywords: -قانون الاسرةالخلع - القانون الجزائري